LOCAL PRODUCT BRANDING STRATEGY TO PENETRATE THE NATIONAL MARKET FROM THE PERSPECTIVE OF CONSUMER PROTECTION LAW AND INTELLECTUAL PROPERTY RIGHTS - Auliya Habibullah1; Madinatul Hasni; Muhammad Abdillah; Wildanur Hafizhah (Academic Solution Publisher, 2025)
In an era of increasingly tight market competition, local products face major challenges to be able to compete at the national level. Branding strategy is an important key in increasing competitiveness, expanding market reach, and building consumer trust. However, the success of this strategy cannot be separated from legal protection, especially in the context of the Consumer Protection and Intellectual Property Rights (IPR) Law. This article aims to analyze how local business actors can design an effective branding strategy by utilizing the legal framework as a basis for protecting and strengthening brand identity. The approach used is qualitative descriptive with a literature study of applicable regulations and case study analysis. The results of the study show that understanding and implementing legal aspects such as trademark registration, industrial design protection, and transparency of product information are determining factors for branding success. The synergy between marketing strategy and legal protection not only maintains product originality, but also increases consumer trust and the competitiveness of local products in the national market.